Pengaruh E-Filing, E-Billing, Literasi Pajak, dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak dengan Kesadaran Pajak sebagai Variabel Intervening pada KPP Pratama Pekalongan. - KUSUMA WIJAYA; Hwihanus (Vokasi : Jurnal Riset Akuntansi, 2026)
This study is motivated by the suboptimal level of taxpayer compliance despite the implementation of digital systems such as e-filing and e-billing. It aims to analyze the effects of e-filing, e-billing, tax literacy, and tax sanctions on taxpayer compliance, with tax awareness as an intervening variable at KPP Pratama Pekalongan. The study employs a quantitative explanatory approach using 300 respondents and analyzes data through PLS-SEM. The results indicate that e-filing, tax literacy, tax sanctions, and tax awareness have a significant positive effect on compliance, while e-billing has no direct effect but becomes significant through tax awareness mediation. The findings suggest that improving compliance requires not only digital system optimization but also strengthening taxpayer literacy and awareness.